Restoring Cultural Heritage: Inner Cities Of Lahore - Ahmed, Zunair; Yasir, Ammar (Winter Journal: IMWI Student Research Journal, 2024)
Restoring cultural heritage in the inner cities of Lahore is essential for preserving the rich history and traditions of this vibrant city. Incorporating traditional elements into modern urban development can enhance the city's unique identity and charm. Integrating historical architecture with contemporary design can create a harmonious blend of old and new, breathing new life into Lahore's inner cities. This fusion of past and present pays homage to the city's heritage and attracts investment and economic opportunities. Active community participation is crucial in the restoration process, as it fosters a sense of ownership and responsibility among residents. Involving local artists, artisans, and historians in conservation projects can preserve authentic cultural practices and skills at risk of being lost. Empowering communities to take pride in their cultural heritage creates a strong sense of belonging and strengthens social cohesion.